ОЦЕНИВАНИЕ СРЕДНЕГО ОСТАТОЧНОГО ВРЕМЕНИ ЖИЗНИ В СПЕЦИАЛЬНОЙ РЕГРЕССИОННОЙ МОДЕЛИ СЛУЧАЙНОГО ЦЕНЗУРИРОВАНИЯ С ДВУХ СТОРОН - Абдикаликов, Ф.; Сейтахов, Р.; Жартыбаев, Ж. (SCIENCE and SOCIETY, 2024)
In this article, we investigate the estimator of the mean residual lifetime in special regression model, when lifetimes are randomly censored on both sides. The asymptotic normality are proved of the estimators and the weakly convergence of an empirical random process to a Gaussian process in Skorokhod space.